Effects of ethnicity and geography on the fecal microbiota and dietary habits of Tibeto-Burman hill tribes in Northern Thailand - Tanapon Seetaraso; Lucsame Gruneck; Vasana Jinatham; Sitanan Kantakat; Marie-Lou Albert; Phatthanaphong Therdtatha; Angkhana Inta; Metawee Srikummool; Jatupol Kampuansai; Siam Popluechai (PLoS ONE, 2025)
Numerous studies have shown that both ethnicity and geography influence gut microbiota composition; however, the effects of these parameters remain understudied in Thailand. We explored the fecal microbiota of 102 individuals, from the Tibeto-Burman-speaking hill-tribe populations (Akha, Lahu, and Lisu) residing in two provinces of Northern Thailand, Chiang Mai, and Chiang Rai, using quantitative PCR polymerase chain reaction. Multivariate statistical analyses, including multiple factor analysis and partial least squares discriminant analysis, were conducted to explore associations between microbiota composition, ethnicity, geographic location, and other host variables (dietary behaviors and participant characteristics). Both ethnicity and geography were linked to gut microbiota composition and dietary patterns, with geography exhibiting a stronger association with variations in microbiota. Ethnicity, however, was primarily related to differences in dietary habits. Notably, gut microbiota profiles were more closely aligned among ethnic groups within the same location than among individuals of the same ethnicity from different regions. The relationship between diet and gut microbiota varied across ethnic and geographic groups, while host factors had a relatively minor impact on microbiota variation. These findings contribute to a broader understanding of variations in gut microbiota among ethnic groups in Northern Thailand and highlight a notable association between geographic location and gut microbiota composition.